Value of Courier Delivery Characteristics Impact to Purchase Intention and Brand Trust - Ratchasuk, Khomkrit; Wanarat, Sawat (Business Administration and Management Journal Review, 2021)
The objectives of this research are to study the level of value and impact of courier delivery characteristics on purchase intention and brand trust. The samples of 400 people. The statistic for data analysis was Percentage, Mean, Standard Deviation, and the Structural Equation Model. The result showed that most of samples were bachelor's degree education or higher, and had income under 50,000 THB/month. Level from factor of value of courier delivery characteristics, economically accessible price, trustful relation with courier, operation flexibility and implement of drop-pick up box were high and order visibility is very high. Level of purchase intention and brand trust were high. Structural equation modeling analysis that the model fit into the empirical data (X2/df = 1.750, GFI = 0.961, AGFI = 0.942, NFI = 0.947, RFI = 0.932, IFI = 0.977, TLI = 0.970, CFI = 0.976, RMSEA = 0.430) and found that of value of courier delivery characteristics had positive impact on purchase intention